A Conceptual Metaphor on the Expression of Apology: A Case Study of the Indonesian Lawyers Club Discussion (A Cognitive Linguistic Study) - Imam Musyayyab; Sailal Arimi (Talenta Publisher, 2022)
In general, apology used as a way to improve relations between individuals. However, in certain contexts, apology can be used as a political tool that has tendencies based on interests, especially group interests. This is illustrated by the expression of invited guests in the Indonesian Lawyers Club (ILC) discussion with the theme